Michael Dukakis Rally at Fresno Amtrak Station - Watkins, Howard::::::::: (1988)
Close-up of Michael Dukakis speaking on dais; others include: ?, U.S. Senator Alan Cranston, ?, ?, Juan Arambula, ?, Lt. Governor Leo McCarthy, Gary Condit, ?, Congressman Richard Lehman, Assemblymember Bruce Bronzan, Mary Bronzan, and Chloe Bronzan